2019
DOI: 10.2139/ssrn.3418106
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Kagan Cooperative Learning Structures in Teaching Subject–Verb Agreement among Rural Sarawak Learners

Abstract: Even after undertaking years of formal education to acquire the language in schools, having a poor command of English remains a problem faced by most Malaysians, especially students in rural schools of Sarawak. Based on the error-analysis carried out by recent research, subject-verb agreement (SVA) is one of the most frequent errors committed by students. To overcome this problem, teachers should significantly improve students' mastery of SVA in the English language through effective teaching methods. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, the subject of the studies were college students. For example, the studies of Xin and Yunus (2019) and Cottell andBarbara (1994) showed that Cooperative Learning Structures are beneficial for students because students' SVA test achievement improves significantly. It can improve the students' language skills, teamwork and also interpersonal skills.…”
mentioning
confidence: 99%
“…However, the subject of the studies were college students. For example, the studies of Xin and Yunus (2019) and Cottell andBarbara (1994) showed that Cooperative Learning Structures are beneficial for students because students' SVA test achievement improves significantly. It can improve the students' language skills, teamwork and also interpersonal skills.…”
mentioning
confidence: 99%